2019
DOI: 10.5604/01.3001.0013.3542
|View full text |Cite
|
Sign up to set email alerts
|

The Satisfaction of Producers, Selling in Various Marketplaces – Results of a Primarysurvey From Hungary

Abstract: Scientific interest in short supply chains (SSC) and local food has increased in the past decade. Due to the concentration of trade, sale opportunities for small sized agricultural producers has decreased. Short supply chains can offer alternate opportunities for them in trading. Therefore, it is necessary to examine their profitability and role in rural development. In the article, producer satisfaction with marketplaces, by means of primary survey is investigated. The sample area consisted of marketplaces wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Similar results were shown by Low and Vogel [27], according to which local food trade provided opportunities for economic development, mostly in urban areas [23]. Kiss [38] conducted a quantitative survey with 214 small produces selling in the Central Hungarian region and Heves county, which is a part of the North Hungarian region (overlapping with the sample area of our current research.). According to his results, the producers' markets around Budapest (the Hungarian capital) were a more suitable commercial alternative for small producers selling directly (compared to conventional marketplaces and market halls.)…”
Section: The Role Of Short Supply Chains In Rural Developmentsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were shown by Low and Vogel [27], according to which local food trade provided opportunities for economic development, mostly in urban areas [23]. Kiss [38] conducted a quantitative survey with 214 small produces selling in the Central Hungarian region and Heves county, which is a part of the North Hungarian region (overlapping with the sample area of our current research.). According to his results, the producers' markets around Budapest (the Hungarian capital) were a more suitable commercial alternative for small producers selling directly (compared to conventional marketplaces and market halls.)…”
Section: The Role Of Short Supply Chains In Rural Developmentsupporting
confidence: 78%
“…However, a larger population, and potentially higher income levels and population densities presumably result in higher absolute territorial demand than, a small-village area. Based on the findings of Schupp [37], and the experiences of a previous study [38] (whose area overlaps the current sample area), SFSC channels (such as well-functioning producers' markets) are rare in a rural or less developed area. According to Low and Vogel [27], local food trade has mostly provided opportunities in urban areas for economic development.…”
mentioning
confidence: 80%
“…On the other hand, the type of marketplaces -and not solely their geographic location -was (and still is) dominant in this relation. According to my previously published results (Kiss, 2019), these same producers were significantly more satisfied with the producers' markets (located in the area of Budapest). There was no significant difference in the satisfaction of the producers in the traditional markets and market halls in the urban-rural context.…”
Section: Discussionmentioning
confidence: 58%
“…According to previously published results of this same research (Kiss, 2019), the spatial (urbanrural) location of the marketplaces was important primarily because the examined producers' markets were concentrated in the Budapest area. The presence of producers' markets was the cause of the higher producers' satisfaction from the Budapest agglomeration in the sample.…”
Section: Resultsmentioning
confidence: 80%
“…Studies indicated that rational and ethical approach parameters such as satisfaction, attitude, social atmosphere, and economic are the factors responsible for producers’ perceptions in the agricultural sector (Govindasamy et al 2003 ; Adrian et al 2005 ; Kiss 2019 ; Valizadeh et al 2018 ; Nguyen et al 2021 ). Furthermore, environmental awareness and perceived quality have been identified as the primary factors influencing the producers’ behavior in the food sector (Bossle et al 2015 ; Silva et al 2020 ; De Canio et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%